On creditor's supplemental rights - Radović Vuk; Tesić Nenad (Anali Pravnog Fakulteta u Beogradu, 2015)
In this paper, the authors introduce a notion of creditor s supplemental rights that so far has been insufficiently explored by legal theory. The authors see the supplemental rights as a variety of subordinated (secondary) rights that commonly with creditor s principle right (main prestation) stands on the active side of an obligational relationship (obligation in a wider sense). Such rights follow the faith of the principal right, whereby they may not be disposed of separately. In addition to the circumstances of their onset by operation of law and their limited duration, a joint characteristic of such rights is the absence of their correlation with the debtor s duties. If we may say that these qualities appear with other secondary rights (Lat. genus proximum), one feature distinguishes supplemental rights from the other of the similar kind - an influence on debtor's proprietary sphere. Through this influence the supplemental rights indirectly assure a claim, contributing thereby to accomplishment of the (subsidiary) goal of an obligation - satisfaction of claim - by either removing the obstacles for the satisfaction, or by preserving and strengthening the prospects for such satisfaction (Lat. differentia specifica). Accordingly, the authors recognize three separate types of supplemental rights: rights by which a creditor removes obstacles for the satisfaction of claim; rights by which a creditor protects his prospects for the satisfaction of claim; and rights by which a creditor enhances his prospects for the satisfaction of claim. .